Determination of Pesticide Residues in Sediments of River Ravi - Arooj Tariq; Sana Akhtar (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2022)
Sediments are socioeconomic, geomorphologic, and an important environmental resource.  The purpose of this study was to determine the pesticide residues in the sediments of River Ravi. For analysis 12 sediment samples were collected along with River Ravi, reaching from Ravi Siphon to BS (Balloki Suleiman) link.  River Ravi is enlisted as one of the most polluted rivers of Pakistan followed by extreme flow variations, i.e. 10 – 10,000 m3/s. The concentration of pesticide residues in samples was detected by the High-pressure liquid chromatography (HPLC) technique. Noticeable concentrations of pesticides were detected in the majority of the samples which depicted high toxicity levels of pesticides in the sediments of River Ravi. High amounts of pesticides were observed in the right and left banks of Saggian (S4) i.e. 11.37 mg/kg and Khudpur (S6, S7) i.e. 12.116 mg/kg. A significant amount of Imidacloprid and Bifenthrin was detected in the majority of the sediment samples, i.e. 22.78 mg/kg and 15.82 mg/kg. Furthermore the detected concentration of pesticides in the right and left bank of Balloki head works (S10, S11) and Ravi Bridge (S3) was relatively less as compared to other sampling sites. All these sampling points receive irrigational runoff from nearby agricultural lands and urban wastewater, resulting in the accumulation of pesticides in the sediments. The following trend of pesticide contamination was observed in the sediment samples of River Ravi, Bifenthrin > Imidacloprid > Dimethomorph > Glyphosate.